DESIGNING LECTORA INSPIRE – BASED MATRIX LEARNING MATERIAL FOR SENIOR HIGH SCHOOL STUDENT AT GRADE XI - Nurul Hamdinesha; Rosliana Siregar; Syahlan (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
The government limited social activities during the Covid-19 pandemic; as a result, the learning process was no longer carried out face to face. Therefore, an appropriate alternative was needed to facilitate the learning process. This study aimed to design valid Lectora Inspire–based matrix learning materials for grade XI high school students. This research was part of development research utilizing the 4D model by Thiagarajan. However, this study was limited only to the defining and designing stages. The defining and designing stages were conducted through a literature review followed by measuring the level of validation of the Lectora Inspire–based learning materials. This research was conducted for three months, from July to October 2020. The instrument used was a validation sheet given to four material experts and two media experts for the Lectora Inspire–based learning materials. The results showed that the learning materials developed based on Lectora Inspire had met the valid requirements. The results of observations from the validators toward the materials and media showed good scores after the materials were revised as suggested by the validators. The Lectora Inspire–based learning materials developed had many advantages compared to learning materials created using other programming applications.